Shallow seismic data acquisiction and processing on the bucaramanga fault in piedecuesta (Santander) (2010)
The active, 220 km-long, left-lateral Bucaramanga Fault traverses the metropolitan area of Bucaramanga(Colombia), home to over 1.5 million people. Imaging the shallow geometry of this fault is crucial forunderstanding the recurrence of seismogenic tectonic processes that may have occurred in the recent geological past. Industry seismic sections across this fault do not resolve shallow strata; collection of high- resolution seismic data across the fault zone is of paramount relevance. In this work, a 2D high-resolution shallow seismic experiment (reflection seismic) is underway. An 18 lb sledgehammer is being used as energy source, generating seismic pulses with frequencies between 10 and 200 Hz. Data are being recorded with a 32 channel digital system. This equipment allows acquisition of both seismic data at sampling rates up to 0.25 milliseconds. Data was processed using hardware and software available at the INSTITUTO COLOMBIANO DEL PETROLEO of ECOPETROL. This project uses concepts and technology from oil industry and applying them to socially significant geological problems.